Current Government Actions and Potential Policy Options for Reducing Obesity in Queensland Schools - Naser A. Alsharairi (MDPI AG, 2018)
School nutrition policies provide promising avenues towards the improvement of children's eating habits and the prevention of obesity. Childhood obesity rates and related chronic diseases are increasing in Queensland, in part as a result of unhealthy eating habits and lack of physical activity. There is a very high investment by the Queensland government in maintaining healthy weight and promoting nutrition and physical activity among schoolchildren through delivering a range of initiatives across the state. However, there is a lack of evidence concerning the effectiveness of nutrition/physical education and parental involvement programs addressing obesity delivered in Queensland schools. This paper can be used to guide government and policy-makers regarding the most effective policy options that will promote healthy eating and physical activity among Queensland schoolchildren. The aim of this paper is to: (i) summarize current evidence on Queensland government responses to obesity; and (ii) discuss potential policy options that could support healthy eating and regular physical activity, and examine the evidence base for each option and suggest new areas for future research.